Respuesta :

Answer:

y-⁸y³x⁰x-²

=y-⁵x-2

=1/y⁵×1/x²

=1/y⁵.x²(Option c)

Answer:

First option and third option

[tex]{ \tt{ {y}^{ - 8} {y}^{3} {x}^{0} {x}^{ - 2} }} \\ \\ { \tt{ = \frac{ {y}^{3} }{ {y}^{8} {x}^{2} } }}[/tex]

• from law of indices:

[tex]→ \: { \boxed{ \tt{a {}^{ - n} = \frac{1}{ {a}^{n} } } \:}}[/tex]

• again from law of indices:

[tex]→ \: { \tt{ {a}^{n} \times {a}^{m} = {a}^{(n + m)} }}[/tex]

Therefore:

[tex]{ \tt{ = \frac{ 1 }{ {y}^{5} {x}^{2} } }} \\ \\ = { \tt{ {y}^{ - 5} {x}^{ - 2} }}[/tex]